Mapping the Impact of Strategic Leadership on Organizational Performance: A Systematic Literature Review - Septiany, Sheila; Erica, Herlis; Aseanty, Deasy; Anggiani, Sarfilianty; Mulyadi, Mulyadi (Dinasti Publisher, 2025)
This study investigates the dynamic relationship between strategic leadership and organizational performance through a Systematic Literature Review (SLR) of 22 peer-reviewed articles published between 2015 and 2025. It highlights how strategic leadership influences organizational outcomes through mediating factors such as innovation capability, identity framing, digital readiness, emotional intelligence, and perceived organizational support. Using the PRISMA protocol and Scopus-indexed sources, the review combines bibliometric mapping and thematic synthesis to reveal conceptual linkages, thematic clusters, and methodological gaps in the existing literature. Findings suggest that strategic leadership plays a pivotal role not only in setting organizational direction and driving innovation intensity but also in cultivating adaptive, inclusive cultures amid uncertainty. The study culminates in an integrative conceptual framework that redefines strategic leadership as a multidimensional catalyst for sustainable performance, offering a consolidated theoretical foundation and actionable guidance for scholars and practitioners navigating the VUCA business landscape.